Epigraphy and History of The Mausoleum Of Abu Bakr Kaffal Shashi - Nematullo Mukhamedov; Nurulloh Turambetov (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2024)
The Hast Imam Complex (Hazrati Imam) is one of the most significant cultural treasures of Tashkent, serving as the religious heart of the capital. It developed around the tomb of the great saint and the first imam of Tashkent, Abu Bakr Muhammad Kaffal Shashi. Abu Bakr Muhammad Kaffal Shashi was one of the early imams of the Muslim world, a renowned scholar, and an expert in the Quran, hadith, Islamic law, and lexicology. He passed away in 976/77, and his grave became a revered pilgrimage site. Alongside Imam al-Bukhari, at-Tirmidhi, and al-Maturidi, Imam Abu Bakr Kaffal Shashi (904-977) holds a special place in the Islamic world. His contemporaries respectfully referred to him as "Hazrat Imam" ("Holy Imam"). The architectural complex of religious buildings near Karasaray Street in Tashkent evolved over the 16th to 21st centuries around the tomb of the esteemed Islamic preacher and Tashkent imam, Kaffal Shashi, who lived in the 10th century. "Hazrati Imam" translates to "Holy Imam." The Muslim pilgrimage to Imam Kaffal Shashi's tomb has a millennium-long history. The original crypt has not survived; the existing mausoleum was constructed in 1542 by the khan’s architect of the time, Ghulam Husain, and is an asymmetrical domed portal mausoleum, known as a khanqah. The khanqah was designed to house pilgrims in residential cells, or hujras. Since the 16th century, when the mausoleum over Hazrati Imam's tomb was erected, other religious structures began to be built nearby. Following the Uzbekistan government's decision to restore the sacred site of Hazrati Imam, extensive restoration works began immediately. The Kaffal Shashi Mausoleum was also restored, with its domes repainted, and its weathered walls rebuilt. As the mausoleum of Kaffal Shashi remains a holy pilgrimage site, new structures were constructed around it, integrating into a single architectural ensemble. This article examines the activities of Abu Bakr Kaffal Shashi, as well as the history of his mausoleum and the epigraphic inscriptions on it.